Predictors of Quality of Life in Pregnant Women Visiting Health Centers of Tabriz, Iran - Somayeh Zarei; Mojgan Mirghafourvand; Sakineh Mohammad-Al; Fatemeh Effati- Daryani; Fatemeh Shiri-Sarand (Mashhad University of Medical Sciences, 2018)
Background & aim: To have successful pregnancy, it is necessary to focus on the mother's quality of life during pregnancy. This study was conducted to determine the predictors of quality of life among Iranian pregnant women.  Methods: This cross-sectional study was conducted on 565 pregnant women visiting health centers of Tabriz, Iran, 2015. The participants were selected using the cluster sampling method. Data were collected using socio-demographic and obstetrics characteristics questionnaire, Edinburgh Postnatal Depression Scale, and a specific questionnaire for quality of life in pregnancy. Data were analyzed by SPSS, version 16. General linear model was used to estimate the effects of the independent variables (depressive symptoms and socio-demographic and obstetrics characteristics) on the dependent variable (quality of life). Results: The mean of the total score of quality of life was 2.9±0.3 from the achievable score range of 0-4. There was a significant negative correlation between depressive symptoms and quality of life (r=-0.53, P